Opinions about the 1991 tax reform, September 1992 - Svallfors, Stefan (Umeå University, 1998)
Within the framework of the research project 'Opinions about the 1991 tax reform' three surveys were conducted. Two of them were carried out as additional questions to the labour market surveys (AKU) in March and September 1991, and the third, as a mail survey in September 1992. From these three surveys three panel studies are constructed. The questions dealt with the respondent´s opinion about the tax reform, if the tax reform made it easier or more difficult to cope with running expenses, and if the respondent felt as a winner or looser after the reform. Furthermore questions were put about the tax reform´s influence on Swedish economy, if the reform made it more difficult to run away from taxes, if the distribution of the tax burden had become more fair or if it had become more unfair, and if certain groups in society were treated unfairly by the tax reform. A number of questions dealt with measures taken in consequence of the tax reform, such as change of housing, increased or decreased savings, change of work place, or more or less overtime. Background variables include information on gender, age, union membership, education, marital status, number of children living in the household, housing, income and occupation. If the respondent is married or cohabiting there is also information about the spouse´s occupation and income.

Inom forskningsprojektet ”Opinioner kring 1991 års skattereform genomfördes tre undersökningar. Två av dem genomfördes genom tilläggsfrågor i arbetskraftsundersökningarna (AKU) i mars och september 1991 och den tredje genomfördes som en postenkät i september 1992. Från dessa tre undersökningar utformades panelstudier. Frågorna handlar om de svarandes åsikter om skattereformen; om skattereformen ledde till att det var lättare eller svårare att klara av de löpande utgifterna och om de svarande kände sig som vinnare eller förlorare av reformen. Vidare ställdes frågor om skattereformens inflytande på den svenska ekonomin, om reformen gjorde det svårare att undkomma skatt, om fördelningen av skattebördan hade blivit mera rättvis eller orättvis och om vissa grupper i samhället blivit orättvist behandlade av skattereformen. Ett antal frågor ställdes som handlade om vilka åtgärder som var i direkt konsekvens till skattereformen, så som byte av bostad, ökat eller minskat sparande, byte av arbetsplats och ökat eller minskat övertidsarbete. Bakgrundsvariabler inkluderar information om kön, ålder, medlemskap i fackförening, utbildning, civilstånd, antal hemmavarande barn, bostad, inkomst och yrke. Om den svarande är gift eller samboende finns det även information om maken/makans/sambons yrke och inkomst.
Opinioner kring 1991 års skattereform, september 1992
Keywords: taxation; beskattning; Economic conditions and indicators; Ekonomiska förhållanden och indikatorer; Economic systems and development; Ekonomiska system och ekonomisk utveckling; Social Sciences; Samhällsvetenskap